(untitled) (Vietnam Journal of Community Medicine, 2023)
COVID-19 pandemic situation: The COVID-19 pandemic was first detected in China in December 2019 and quickly entered Vietnam. Quang Nam is one of the provinces heavily affected by the pandemic. However, Quang Nam has achieved remarkable results with a proactive and drastic spirit in pandemic prevention and control. Methodology: A cross-sectional study using data on the number of people isolated, the number of samples tested, and the number of COVID-19 vaccine shots were conducted in Quang Nam. Results: Isolate 80,357 people to prevent the pandemic from spreading, of which: 10,539 people in 2020 (13.1%) and 69,818 people in 2021 (86.9%); Testing capacity was increasingly improved with 701,248 test samples taken, of which 102,267 test samples in 2020 (14.6%) and 598,981 samples in 2021 (85.4%); The rate of people aged 18 years and over receiving at least one shot of vaccine reached 99.1%, the number of people receiving the full bare shot got 86.8%, the number of people who received the booster shot advanced 0.1%, the results of vaccination for children aged 12-17 needing to be vaccinated 86.1%. Conclusions: Quang Nam’s epidemic prevention and control activities in the two years 2020-2021 focused on three main activities: isolating to prevent the spread of the disease, testing to detect cases and covering vaccination for people.